Zapleteni zemljepis demokratizacije - Maver, Aleš (Studia Historica Slovenica, 2022)
The contemporary discussion of democratic movements during the late 1980s and early 1990s stresses need to place these development a in a broader context, comprising different historical experiences, dating at least to the beginning of the WWII, the stages of the processes itself, as well as their aftermath. Regarding the historical experiences, a few characteristics have to be singled out. For instance, inability or unwillingness of Soviets to take the historical differences in their domain into account greatly contributed to the pretty early and unexpected demise of their empire. Greater emphasis should further be placed on the differences between the Soviet republics themselves. It's clear that an uneasy task to balance national emancipation and democratization was undertaken almost everywhere in the late 1980s. But failure of democratization in Russia must be regarded as a key development. The transitions to democracy in former Yugoslav republics followed different patterns as well.
Keywords: 20. st.; Belarus; Belorusija; breakup of Yugoslavia; democratic movements in Central and Eastern Europe; democratization; demokratična gibanja; demokratizacija; politične razmere; razpad Jugoslavije; Soviet Union; Sovjetska zveza; Srednja Evropa; Ukraine; Ukrajina; Vzhodna Evropa